KONSEP MUHAMMAD HATTA TENTANG IMPLEMENTASI PANCASILA DALAM PERSPEKTIF ETIKA PANCASILA - Sri Soeprapto (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2013)
All nations may have similarities and differences in value systems. The values, which are considered noble by each nation's culture, are generally similar, but the hierarchy of believed values is different. The hierarchy of values is a specific historical product of each nation. Hatta explained that main ideas of Pancasila as the state ideology is formulated in the Preamble of the Constitution (Undang-Undang Dasar 1945). An issue that should be considered is to formulate Pancasila as an ethical norm of Indonesian life. The ethical norm is formed as the basic for building Indonesians dignity in the future. The ethics of Pancasila is an ethical norm as a guidance for the State and people of Indonesia in implementing Pancasila. In implementing Pancasila, the State must provide a guarantee for people of Indonesia in practicing their religious beliefs, obtaining a decent livelihood and their human rights, promoting the establishment of unity in diversity, majoring consultative dialogue and rejecting authoritarianism, and also actualizing the social justice through political and economical justice.